(untitled) ("Conference on Universal Science Research 2023", 2026)
An abbreviation is a language unit used to express a long word or phrase in a short form. Abbreviations are widely used in the language to shorten words or phrases, simplify their pronunciation or generalize. They help speed up language communication and increase efficiency. The article analyzes the lexical-semantic and structural features of the lexical combinations of the semantic field «TV» in Uzbek and English (as an example of abbreviations), and also focuses on the issues of studying abbreviations in linguistics.